2021
DOI: 10.3390/plants10061116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity, Linkage Disequilibrium and Population Structure of Bulgarian Bread Wheat Assessed by Genome-Wide Distributed SNP Markers: From Old Germplasm to Semi-Dwarf Cultivars

Abstract: Genetic diversity and population structure are key resources for breeding purposes and genetic studies of important agronomic traits in crops. In this study, we described SNP-based genetic diversity, linkage disequilibrium and population structure in a panel of 179 bread wheat advanced cultivars and old accessions from Bulgaria, using an optimized wheat 25K Infinium iSelect array. Out of 19,019 polymorphic SNPs, 17,968 had а known chromosome position on the A (41%), B (42%) and D (11%) genome, and 6% were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 54 publications
2
26
1
Order By: Relevance
“…This likely drove the observed increase in the relative value, given the inherent increase in genetic diversity of a seed grown plant, compared to clonal plants derived from cuttings. Overall, the average genetic distance values obtained for the remaining varieties were consistently low when compared to other studies in wheat, which describe D values from 0.1 to 0.5 across roughly 150 wheat accessions [ 14 , 15 ]. Nevertheless, this analysis highlighted the limited genetic distance between the Cannabis varieties CBD1 and CBD2 in particular, and to a lesser degree, the Motavation and Blue Venom varieties.…”
Section: Resultscontrasting
confidence: 59%
“…This likely drove the observed increase in the relative value, given the inherent increase in genetic diversity of a seed grown plant, compared to clonal plants derived from cuttings. Overall, the average genetic distance values obtained for the remaining varieties were consistently low when compared to other studies in wheat, which describe D values from 0.1 to 0.5 across roughly 150 wheat accessions [ 14 , 15 ]. Nevertheless, this analysis highlighted the limited genetic distance between the Cannabis varieties CBD1 and CBD2 in particular, and to a lesser degree, the Motavation and Blue Venom varieties.…”
Section: Resultscontrasting
confidence: 59%
“…The DNA of the 80 genotypes was sent to Trait Genetics (Gatersleben, Germany) for genotyping-by-sequencing using a 25K Infinium iSelect array. Extensive details on the development of the 25K wheat Infinium array were reported by Aleksandrov et al (2021). The array genotyping revealed 21,450 singlenucleotide polymorphisms (SNP) markers that were used to calculate the genetic distance among the selected genotypes using the R-package "ade4" as described by Dray and Dufour (2007).…”
Section: Analysis Of the Genetic Diversitymentioning
confidence: 99%
“…Results of this study were consistent with the findings of Chao et al (2010 ) and Ladejobi et al (2018 ) reported the LD decay of 6.4, 4.5, 4, and 4.98 Mbp for A, B, D, and whole-genome, respectively. Aleksandrov et al (2021) performed a study on Bulgarian bread wheat germplasm to dissect the population structure and linkage disequilibrium on two populations, including one population of old germplasm and one set of modern semi-dwarf cultivars. Old germplasm showed an LD decay of 3.6, 3.3, 3.1, and 3.3 Mb in subgenomes A, B, and D and the whole-genome, respectively.…”
Section: Discussionmentioning
confidence: 99%